Competencies achievement of BRAC NFPE students improving - Nath, Samir Ranjan; Shahjamal, Mirja M (BRAC Research and Evaluation Division (RED), 2019)
Competency achievement of the students of BRAC non- fonnal primary schools at the end of their primary cycle was assessed and reported in this article. Four cohorts of students were considered and brought under assessment at the end of respective academic cycle. They are the students of second, third, fourth and fifth batches completing the courses between 2000 and 2003. The findings reveal that overall perfonnance of the NFPE graduates increased over time. The graduates of the recent years are getting more homogeneous than the previous years and inter-school variation significantly reduced over the period. Gender difference in achievement also decreased recently. A collective effort of the teachers, programme organisers and the management was urged to keep this trend on.